Biodegradable Particles as Vaccine Delivery Systems: Size Matters - Joshi, Vijaya B. (Springer US, 2012)
Poly(lactide-co-glycolide) (PLGA) particles have strong potential as antigen delivery systems. The size of PLGA particles used to vaccinate mice can affect the magnitude of the antigen-specific immune response stimulated. In this study, we fabricated and characterized 17 μm, 7 μm, 1 μm, and 300 nm PLGA particles coloaded with a model antigen ovalbumin (OVA) and CpG oligodeoxynucleotides (CpG ODN). PLGA particles demonstrated a size-dependent burst release followed by a more sustained release of encapsulated molecules. PLGA particles that were 300 nm in size showed the highest internalization by, and maximum activation of, dendritic cells. The systemic antigen-specific immune response to vaccination was measured after administration of two intraperitoneal injections, 7 days apart, of 100 μg OVA and 50 μg CpG ODN in C57BL/6 mice. In vivo studies showed that 300 nm sized PLGA particles generated the highest antigen-specific cytotoxic T cell responses by days  14 and 21. These mice also showed the highest IgG2a:IgG1 ratio of OVA-specific antibodies on day  28. This study suggests that the smaller the PLGA particle used to deliver antigen and adjuvants the stronger the antigen-specific cytotoxic T cell response generated.